Chemorheology and ultimate behavior of epoxy-amine mixtures modified with a liquid oligomer - Aizpurua, B. (2000)
Rubber toughening of epoxy resins has been actively studied since the 1960s with clear progress in understanding of the ultimate properties: microstructure relationships. The morphology, obtained after curing of the modified thermosetting matrix, is a function of the process conditions as well as of the materials used because both influence the thermodynamics and the kinetics of phase separation. In this work several amounts of poly(oxypropylentriamine) (POPTA), have been added as modifier to a diglycidyl ether of bisphenol-A (DGEBA)-based epoxy matrix cured with a cycloaliphatic amine. Molecular weight of the neat resin and amine/epoxy stoichiometric ratio have also been used as variables. This investigation has focused upon the importance of cure chemorheology for microstructure formation by using both physicochemical (isothermal and dynamic calorimetry) and rheological techniques. In the second part of this study, the influence of the molecular weight of the epoxy resin in the ultimate properties of 15 wt % POPTA-modified epoxy matrices is also analyzed.